Sensory analysis of foods of animal origin - Nollet, Leo M. L., 1948-; Toldrá, Fidel (CRC Press, 2011)
When it comes to food selection, consumers are very reliant on their senses. No matter the date on a carton of milk or the seal on the package of meat, how that milk smells and the color of that meat are just as critical as any official factors. And when it comes to meal time, all the senses must conspire to agree that taste, smell, color, and texture are appealing. Fidel Toldrá was named 2010 American Meat Science Association Distinguished Research Award recipient Compiled by two of the most esteemed researchers in the food science industry, Leo M.L. Nollet and Fidel Toldrá, Sensory Analysis o.